Evaluation Of Sound Absorption Of Micro Perforated Panel Made By Palm Oil Fiber - Zainal Abidin, Nur Sarah (Universiti Sains Malaysia, 2022)
Nowadays, the urban areas are prone to the negative effects of noise pollution as a result of rapid development of transportation, industrialisation, and urbanisation. Therefore, the regulation of noise is extremely important and needs to be handled. Micro-perforated panels (MPP) can be a promising method to minimise noise on a significant basis. Therefore, the purpose of this study is to determine the effect of using Oil Palm Fibre as MPP and the size of the perforations in terms of the sound absorption coefficient. This will allow the sound absorption performance of MPP to be improved. In the first step of the process, the samples are made from oil palm fibre and then perforated using a Computer Numerical Control (CNC) machine with a hole diameter of 1 mm. Following that, an experiment using impedance tube is performed. The results of the measurements demonstrate that the sound-absorbing panel with MPP structure creates a better acoustic performance than the sound-absorbing panel without MPP structure. Using the Maa prediction model as a theoretical basis, the MATLAB software was used to simulate the sound absorption performance of each possible scenario. According to the findings, the peak value of the sound absorption coefficient (SAC) increases when there is an increase in both the thickness and size of the perforations. Furthermore, it moves the peak towards the higher frequency range, which in turn reduces the bandwidth. According to the findings MPPs have the potential to be used in commercial sound absorbers by modifying the size of the perforations in the material. The findings also demonstrated that the MPP structure possesses the potential in improving the sound absorption efficiency of oil palm fibre within a particular frequency.